COVID-19 Patient Vaccine Program Design and Implementation: An Academic Children's Hospital's Model, Approach, and Outcomes. Issue 2 (April 2022) - Boogaard, Claire O'Connell; Graves, Teresa; Ricks, Jeanne R.; Badh, Ranjodh; Cronin, Bridget; Koay, Wei Li Adeline; Hanisch, Benjamin; Rahn, Katie; Williams, Andrew R.; Gorman, Kathleen; Shah, Rahul K.; Biddle, Cara L.
Abstract : To slow the spread of the 2019 novel coronavirus disease (COVID-19) and reduce the associated morbidity and mortality, the Children's National Hospital developed a multidisciplinary, collaborative vaccine program aimed at equitably and expeditiously vaccinating the pediatric population of the surrounding community. Interdepartmental collaboration, professional expertise, and community partnerships allowed for a dynamic and successful program design that began as large volume–centralized vaccine clinics and expanded to smaller volume ambulatory clinics. This strategy proved successful at meeting local vaccine demand; however, strategies to improve vaccine uptake in communities with high rates of hesitancy are still needed to maximize vaccine equity.